Children's and adolescents' digital access in Chile: the role of digital access modalities in digital uses and skills. Issue 2 (3rd April 2021) - Cabello, Patricio; Claro, Magdalena; Rojas, Rodrigo; Trucco, Daniela
ABSTRACT: This article analyses the modes of physical access that facilitate participation in digital opportunities and the development of digital skills in children and adolescents (9 to 17 years old). We analysed the data obtained from the Kids Online survey in Chile. A latent class analysis (LCA) was conducted to identify groups based on access points and devices of use; access modalities were then composed crossing these variables. Four access modalities were found: cellphone-home; cellphone-ubiquitous; multi-device-home; multi-device-ubiquitous . Multiple logistic regression analysis showed that ubiquitous modalities ( multi-device and cellphone varieties) predicted digital use and skills among young Chileans, while the more static modalities ( cellphone and home and multi-device and home ) did not. These results are critical to addressing what can be defined as "enabling access" among young Internet users in the context of digital inclusion policies.